Kepemimpinan Yosua Dalam Pelayanan: Strategi Inspiratif Dan Pembelajaran Praktis Bagi Pemimpin Gereja Masa Kini - Lusia Rante Tasik; Afriwati Tande; Valmin Mastuti; Silvita Samana (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The story of Joshua's leadership in the Bible provides valuable insight for modern church leaders. Through vision analysis, relational leadership, handling challenges, conflict management, and Joshua's mentoring, this paper explores leadership principles that can be applied in today's spiritual ministry. Case studies and interviews with church leaders provide concrete examples of the application of these principles in practical contexts. The relevance of Joshua's leadership strategy in facing contemporary dynamics and the need for contextual adjustments is explained. The conclusion states that Joshua's story provides a foundation for inspired and practical church leadership, promoting the continuity of spiritual ministry in changing times.